Prognosis of patients receiving intensive care for lifethreatening medical complications of haematological malignancy. Issue 6628 (9th April 1988) - Lloyd-Thomas, A R; Wright, I; Lister, T A; Hinds, C J
Abstract : The mortality of patients admitted to intensive care units with haematological malignancy is high. A humane approach to the management of the critically ill as well as efficient use of limited resources requires careful selection of those patients who are most likely to benefit from intensive care. To delineate more accurately the factors influencing outcome in these patients the records of 60 consecutive admissions to the intensive care unit (37 male, 23 female) with haematological malignancy were reviewed retrospectively. Fifty patients were in acute respiratory failure, most commonly (34 patients) with a combination of pneumonia and septicaemic shock. The severity of the acute illness was assessed by the APACHE II (acute physiology and chronic health evaluation II) score and number of organ systems affected. Thirteen patients survived to leave hospital. The mortality of patients with haematological malignancy was consistently higher than predicted from a large validation study of APACHE II in a mixed population of critically ill patients. Moreover, no patient with an APACHE II score of greater than 26 survived. Mortality among the 22 patients with relapsed malignancy (21 deaths), was significantly higher than among the 35 patients at first presentation (26 deaths). On discharge from the intensive care unit all survivors had responded well to chemotherapy and had normal or raised peripheral white cell counts. They included seven patients who had recovered from leucopenia (white cell count <0.5 × 10 9 /1). In contrast, 36 of the 47 patients who died were leucopenic at the time of death. The overall mortality of critically ill patients with haematological malignancy is higher than equivalently ill patients without cancer. The dysfunction of an increasing number of organ systems, an APACHE II score of greater than 30, failure of the malignancy to respond to chemotherapy, and persistent leucopenia all point to a poor outcome.